2005
DOI: 10.1021/jp0530909
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Low-Energy Chlorophylls in the PSI-LHCI Supercomplex from Chlamydomonas reinhardtii. A Site-Selective Fluorescence Study

Abstract: Almost all photosystem I (PSI) complexes from oxygenic photosynthetic organisms contain chlorophylls that absorb at longer wavelength than that of the primary electron donor P700. We demonstrate here that the low-energy pool of chlorophylls in the PSI-LHCI complex from the green alga Chlamydomonas reinhardtii, containing five to six pigments, is significantly blue-shifted (A max at 700 nm at 4 K) compared to that in the PSI core preparations from several species of cyanobacteria and in PSI-LHCI particles from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
24
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 45 publications
(129 reference statements)
5
24
0
Order By: Relevance
“…However, the spectral region which proved to be the best predictor of Chl a and other pigments was located at much longer wavelengths than PSI reaction center absorption at 700 nm. Mechanistically, light should be absorbed in this spectral region by the small number of specific pigmentprotein complexes, so called Bfar-red chlorophylls^ (Gobets and van Grondelle 2001;Melkozernov 2001;Gibasiewicz et al 2005), which nevertheless could transfer light energy to both PSII and PSI (Oja et al 2004;Pettai et al 2005a,b). The existence of such pigments has been shown and Fig.…”
Section: Discussionmentioning
confidence: 99%
“…However, the spectral region which proved to be the best predictor of Chl a and other pigments was located at much longer wavelengths than PSI reaction center absorption at 700 nm. Mechanistically, light should be absorbed in this spectral region by the small number of specific pigmentprotein complexes, so called Bfar-red chlorophylls^ (Gobets and van Grondelle 2001;Melkozernov 2001;Gibasiewicz et al 2005), which nevertheless could transfer light energy to both PSII and PSI (Oja et al 2004;Pettai et al 2005a,b). The existence of such pigments has been shown and Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The concentrated sample was diluted before the fluorescence experiments in a buffer containing 20 mM Bis Tris (pH = 6.0), 10 mM NaCl, Methods: A diluted sample (OD 676nm,10mm ≈ 0.1) was placed in a (10 mm × 10 mm plastic) cuvette and frozen to 4.2 K in a liquid helium cryostat (Utreks; Kiev, Ukraine). Both FHB and SSF experiments were performed with the setup described previously (Gibasiewicz et al 2005). Shortly, the source of the nonselective excitation at 420 nm in the FHB experiment was a 150-W tungsten halogen lamp equipped with an interference filter (fwhm = 20 nm).…”
Section: Methodsmentioning
confidence: 99%
“…A technique complementary to AHB, also wellestablished, is the fluorescence line narrowing (FLN; Peterman 1998, Pieper et al 2001, Timpmann et al 2004, Gibasiewicz et al 2005, Rätsep et al 2005. In photosynthetic complexes, low temperature emission originates from a distribution of the lowest-energy states.…”
Section: Introductionmentioning
confidence: 99%
“…This particular asparagine is however absence in the LHCA3 homolog of C. reinhardtii. In fact, Gibasiewicz et al (118) showed that C. reinhardtii contains a special set of low-energy chlorophylls that are iso-energenic with the primary donor of PSI, yet retain some of the red chlorophyll characteristics. Furthermore the locations of the "far red like" chlorophylls still need to be identified.…”
Section: Proteins That Are Reduced In Anaerobic High Light Conditionsmentioning
confidence: 99%